Chemokine Receptors as Biomarkers in Multiple Sclerosis - Fox, Robert J. (IOS Press, 2006)
Leukocyte infiltrates characterize tissue inflammation and are thought to be integral in the pathogenesis of multiple sclerosis (MS). This attribute underlines the importance of understanding mechanisms of leukocyte migration. Chemokines are secreted proteins which govern leukocyte trafficking into targeted organs. Chemokine receptors (CKR) are differentially expressed on leukocytes and their modulation is a potential target for MS disease modifying therapies. Chemokines and their receptors are also potential biomarkers of both disease activity and response to treatment. We describe the fluctuations in CKR expression on peripheral leukocytes in a group of MS patients followed longitudinally for up to 36 months. We observed little fluctuation in CKR expression within each patient over time, despite considerable variability in CKR expression between patients. These observations suggest that individual patients have a CKR set point, and this set point varies from one patient to another. Evaluation of chemokines or chemokine receptors as biomarkers in MS will need to account for this individual variability in CKR expression.